Correlation between Post-Thaw Spermatozoa Quality of the Endangered Javan Banteng with OPN Gene Expression - Vincentia Trisna Yoelinda; Raden Iis Arifiantini; Dedy Duryadi Solihin; Muhammad Agil; Dedi Rahmat Setiadi; Tulus Maulana; Bambang Purwantara; Yohana Tri Hastuti; Jansen Manansang; Dondin Sajuthi (Veterinary Medicine International)
The role of ex situ conservation facilities or captivity through captive breeding programs is essential in the conservation of the endangered Javan banteng. The development of semen cryopreservation may assist on one side of the conservation plan. However, the male Javan banteng reproductive capability must be considered as it influences the targeted outputs. Studying the potential biomarker for fertility such as osteopontin gene expression is also expected to help predict male fertility. Therefore, this study aimed to analyze the quality of spermatozoa after thawing to help predict the male reproductive capability of Javan banteng. Furthermore, this study investigated the potential role of osteopontin gene expression in male Javan banteng fertility. A positive reinforcement approach was used to accustom the male and female animals as we focused on establishing a collection procedure using neither sedation nor anaesthesia. Semen samples were collected at Taman Safari Indonesia, Bogor, in accordance with the female banteng receptivity. Semen samples were then evaluated and then cryopreserved under field conditions. Our study showed the different predicted reproductive capability of the Javan banteng based on the post-thaw spermatozoa quality, which showed significant differences. The OPN gene showed positive correlations with the progressive motility (r = 0.711, p = 0.048), viability (r = 0.822, p = 0.012), and acrosomal integrity (r = 0.665, p = 0.072) of Javan banteng spermatozoa after thawing. Our study demonstrated the predicted Javan banteng reproductive capability based on various post-thaw spermatozoa variables. This finding is also the first report on the OPN gene potential to be developed as the assessment tool of post-thaw spermatozoa quality of the male Javan banteng. The findings in our study may help give recommendations for future breeding programs, especially in the ex situ conservation sites.